2020
DOI: 10.3389/fphar.2020.01123
|View full text |Cite
|
Sign up to set email alerts
|

Overview and Analysis of the Cost of Drug Programs in Poland: Public Payer Expenditures and Coverage of Cancer and Non-Neoplastic Diseases Related Drug Therapies from 2015–2018 Years

Abstract: Background: In Poland drug programmes developed by the Minister of Health and financed by the National Health Fund are special reimbursement frameworks of innovative, expensive, and mostly hospital based medical products used for a small number of patients. Research Design: The research presented in this paper is based on data analysis published by the National Health Fund in Poland. The analysis focused on estimating public payer expenditure on drugs available within drug programmes from 2015 to 2018. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…The early implementation of palliative care is requested by the reduced cognitive ability of brain tumor patients [ 9 ] and by the heavy distress that is experienced by caregivers. Moreover, in the context of the heavy socioeconomic burden of cancer [ 10 , 11 ], it has been shown that early palliative care activation reduces the costs of hospitalizations [ 12 ] and leads to an increase in home discharge for end-of-life care [ 13 ]. In most of the cases discussed here, caregivers had to face a sudden worsening of patients’ neurological conditions without having the possibility to set up adequate domestic assistance: this can explain the low rate of home deaths in our series.…”
Section: Discussionmentioning
confidence: 99%
“…The early implementation of palliative care is requested by the reduced cognitive ability of brain tumor patients [ 9 ] and by the heavy distress that is experienced by caregivers. Moreover, in the context of the heavy socioeconomic burden of cancer [ 10 , 11 ], it has been shown that early palliative care activation reduces the costs of hospitalizations [ 12 ] and leads to an increase in home discharge for end-of-life care [ 13 ]. In most of the cases discussed here, caregivers had to face a sudden worsening of patients’ neurological conditions without having the possibility to set up adequate domestic assistance: this can explain the low rate of home deaths in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) is the most common cancer, accounting for 11.7% of all new diagnoses in 2020, and is responsible for 7% of all cancer-related deaths [1] . As such, breast cancer is a serious public health concern and can be responsible for considerable costs in healthcare services [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Excessive alcohol consumption leads to a substantial increase in the number of hospitalization, an increase in social and economic costs and the increase in the prices of alcoholic beverages brings a positive contribution to public health [2,3]. However, a study conducted in 15 Latin American countries tried to make a comparison between the taxes levied on soft drinks and beer.…”
Section: Introductionmentioning
confidence: 99%